2016
DOI: 10.1002/cbdv.201500139
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Composition and Antimicrobial Activities of the Essential Oils of Green Branches and Leaves of Egyptian Navel Orange (Citrus sinensis (L.) Osbeck var. malesy)

Abstract: The essential oils isolated from the leaves and green branches of the Egyptian navel orange trees were analyzed by GC and GC/MS. A total of 33 and 24 compounds were identified from the oils of the leaves and branches accounting for 96.0% and 97.9%, respectively, of the total detected constituents. The major ones were sabinene (36.5; 33.0%), terpinen-4-ol (8.2; 6.2%), δ-3-carene (7.0; 9.4%), limonene (6.8; 18.7%), trans-ocimene (6.7; 6.1%), and β-myrcene (4.5; 4.4%). The antimicrobial activities of both oils we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…The chemical composition of essential oils from C. aurantifolia leaves and fruit peel was similar to the ones from other species of Citrus, such as C. limonia and C. reticulata previously described in the literature since they all have the same major constituents (Martins et al 2017). Limonene was found at large amounts in C. aurantifolia leaves and fruit peel, besides being the major constituent of essential oils from C. sinensis, C. latifolia and C. limonia (Eldahshan andHalim 2016, Estevam et al 2016). Therefore, it should be highlighted that, since essential oils from C. aurantifolia found in southwestern Goiás are rich in limonene, linalool, citronellal and citronellol, they may be a new prospecting source of these bioactive compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical composition of essential oils from C. aurantifolia leaves and fruit peel was similar to the ones from other species of Citrus, such as C. limonia and C. reticulata previously described in the literature since they all have the same major constituents (Martins et al 2017). Limonene was found at large amounts in C. aurantifolia leaves and fruit peel, besides being the major constituent of essential oils from C. sinensis, C. latifolia and C. limonia (Eldahshan andHalim 2016, Estevam et al 2016). Therefore, it should be highlighted that, since essential oils from C. aurantifolia found in southwestern Goiás are rich in limonene, linalool, citronellal and citronellol, they may be a new prospecting source of these bioactive compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Gannan in Jiangxi Province is the top navel orange producing area in China, with an area of 0.11 million hectares and a total annual output of 1.2 million tons. Previous studies indicated that navel oranges contain many useful natural products such as essential oils, flavonoids, carotenoids and vitamins [ 10 , 11 ]. Exploring and exploiting citrus essential oil is an additional way to increase the economic value of the crop due to its special roles in the food, flavor and cosmetics industries.…”
Section: Introductionmentioning
confidence: 99%
“…Benefits of essential oil stem from their reported medicinal uses as antioxidant, antimicrobial and anti-inflammatory properties (Eldahshan 2015;Salleh et al 2015;Eldahshan & Halim 2016;Omri Hichri et al 2016). Cinnamomum (Lauraceae) is a genus of evergreen shrubs and trees.…”
Section: Introductionmentioning
confidence: 99%